Analysis of the efficiency of recognition models in streaming video - V. M. Goryaev; G. A. Mankaeva; D. B. Bembitov; E. V. Sumyanova; R. A. Bisengaliev (Современная наука и инновации)
This article analyzes VGG, MobileNet, and ResNet architectures for medical face mask recognition in streaming video. Deep convolutional neural network is presented by Python libraries: Tensorflow, Keras, and Haar wavelets based on the models of three architectures and their comparative analysis is performed. As a result of the study it was found that the VGGNet method has many times more parameters and is slow to work, while the fastest is Resnet, its accuracy is 97.1% for 30 epochs, and MobileNet - 98.9% for 100 epochs. But according to the results of MobileNet training, it was noticeable that its accuracy increases, and we can conclude that the accuracy will definitely improve if we train on more epochs and photo images, and its compact size allows to use it on devices with modest characteristics.